Evidence Linking the Role of Placental Expressions of Peroxisome Proliferator‐Activated Receptor‐γ and Nuclear Factor‐Kappa B in the Pathogenesis of Preeclampsia Associated With Periodontitis. Issue 8 (1st August 2016) - Mahendra, Jaideep; Parthiban, Prathahini S.; Mahendra, Little; Balakrishnan, Anandan; Shanmugam, Sambandham; Junaid, Mohammed; Romanos, Georgios E.
Abstract : Background: Peroxisome proliferator‐activated receptor (PPAR)‐γ activation leads to suppression of production of a broad range of proinflammatory molecules. It plays a role in differentiation of trophoblasts and helps in normal placentation and formation of vascular exchange interface. Activation of nuclear factor‐kappa (NF‐κ) B triggers proinflammatory molecules inducing abnormal placentation and premature labor. This study aims to explore expression of PPAR‐γ and NF‐κB in placentas of women with periodontitis‐associated preeclampsia compared with that in normotensive pregnant women. Methods: Fifty pregnant women were included. Twenty‐five were controls (normotensive pregnant women) and 25 were pregnant women with preeclampsia, including those with gestational hypertension. Demographic data, pregnancy characteristics, and periodontal parameters were recorded, including: 1) plaque index; 2) gingival index; 3) bleeding on probing (BOP); 4) probing depth; and 5) attachment loss (AL). Placental tissue samples were collected from both groups and analyzed to quantify expression of PPAR‐γ and NF‐κB using real‐time polymerase chain reaction. Results: BOP and AL were significantly higher in pregnant women with preeclampsia compared with normotensive pregnant women ( P <0.05). Expression of PPAR‐γ was downregulated in patients with preeclampsia compared with that of healthy normotensive patients, which was statistically significant ( P <0.05), whereas NF‐κB was significantly activated ( P <0.05) in pregnant women with preeclampsia compared with normotensive pregnant women. Conclusions: Higher periodontal disease prevalence is found among pregnant women with preeclampsia, with increased percentage of sites with BOP and greater AL. This study provides novel information on host response to systemic inflammation induced by periodontal pathogens through mechanisms involving downregulation of PPAR‐γ and increased activation of NF‐κB.